Cystic lymphangioma of the breast. First case in Russian clinical practice - A. D. Zikiryahodzhaev; E. K. Saribekyan; E. A. Rasskazova; D. R. Ortabaeva; D. R. Omarova; S. P. Prokopenko; N. S. Goeva (ABV-press, 2021)
In this article, we review of the existing literature on cystic lymphangiomas and report a case of cystic lymphangioma of the breast in an 83‑year-old patient. This case required differential diagnosis between infiltrative cancer and cystic lymphangioma of the breast. The patient has undergone surgery (tumor removal). No complications were observed.